Impact of Infodemic on Organizational Performance - Bari, Muhammad Waseem (IGI Global, 2021)
COVID-19 is not the only global challenge that the world is facing these days. The infodemic, based on the pandemic (COVID-19), is another serious challenge for the world at this time. Each flare-up is joined with a large volume of data and information; however, this data can be based on deception, gossip, rumors, and more. Misinformation not only impacts the human body negatively but also impacts mental health. The infodemic has an impact on human health and professional performance, but also leaks into business organizations in terms of financial matters, employees' psychological and physica.